THE HISTORY OF STUDYING THE FRONT LETTERS OF UZBEK PARTICIPANTS IN THE SECOND WORLD WAR (American Journal of Interdisciplinary Research and Development, 2022)
The article analyzes the letters of soldiers and officers participating in the Second World War. It also explores the cultural and communicative functions of epistolary messages based on archival materials.